2003
DOI: 10.1099/vir.0.19522-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of attenuation, immunogenicity and efficacy of a bovine parainfluenza virus type 3 (PIV-3) vaccine and a recombinant chimeric bovine/human PIV-3 vaccine vector in rhesus monkeys

Abstract: Restricted replication in the respiratory tract of rhesus monkeys is an intrinsic property of bovine parainfluenza virus type 3 (bPIV-3) strains. This host range phenotype of bPIV-3 has been utilized as a marker to evaluate the attenuation of bPIV-3 vaccines for human use. Two safety, immunogenicity and efficacy studies in primates evaluated and compared three human parainfluenza virus type 3 (hPIV-3) vaccine candidates: biologically derived bPIV-3, a plasmid-derived bPIV-3 (r-bPIV-3) and a chimeric bovine/hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…The levels of hPIV3 HAI and neutralizing antibodies observed for the primate sera obtained from animals immunized with both kinds of b/h PIV3/RSV F vaccines were similar to the titers displayed by rhesus monkeys vaccinated with b/h PIV3 (30). Rhesus monkeys immunized with b/h PIV3 were effectively protected from challenge with wild-type hPIV3.…”
Section: Discussionmentioning
confidence: 57%
“…The levels of hPIV3 HAI and neutralizing antibodies observed for the primate sera obtained from animals immunized with both kinds of b/h PIV3/RSV F vaccines were similar to the titers displayed by rhesus monkeys vaccinated with b/h PIV3 (30). Rhesus monkeys immunized with b/h PIV3 were effectively protected from challenge with wild-type hPIV3.…”
Section: Discussionmentioning
confidence: 57%
“…However, the restricted replication of bPIV3 compared to hPIV3 was previously demonstrated in the respiratory tract of chimpanzees and rhesus monkeys and this attenuation phenotype was shown to correlate with the safety profile of bPIV3 in human infants [29][30][31][32]. We have previously shown that rbPIV3, the virus vector was restricted in replication in the upper and lower respiratory tract of rhesus monkeys compared to hPIV3, and that replacement of the bovine PIV3 F and HN gene with human PIV3 F and HN resulted in an intermediate level of attenuation [33]. Here, we compared the replication of the chimeric b/h PIV3/hMPV F2 virus with wt hPIV3, recombinant bPIV3 (rbPIV3) and a bovine parainfluenza virus expressing the human PIV3 F and HN genes (b/h PIV3) in the respiratory tract of rhesus monkeys.…”
Section: Introductionmentioning
confidence: 87%
“…However, the titers between b/h PIV3/hMPV F2 and b/h PIV3 or rbPIV3 in the URT and LRT were not significantly different (P > 0.05). Therefore, b/h PIV3/hMPV F2 replicated to the same level as rbPIV3, a virus that was attenuated and safe in human infants [31][32][33].…”
Section: B/h Piv3/hmpv F2 Displayed Host-range Restricted Replicationmentioning
confidence: 94%
“…Further, there is rapid virus clearance and limited virus replication, which are ideal qualities for a vaccine vector. A construct with bPIV3/hPIV3 chimeric virus (2, 71) as a vector backbone with the F and HN glycoproteins from hPIV3 has been evaluated as a vaccine against hPIV3 (26,54). A construct consisting of bPIV3 as a backbone with F and HN proteins from hPIV3 and F protein from RSV was also generated.…”
Section: Discussionmentioning
confidence: 99%